2022
DOI: 10.1097/cce.0000000000000618
|View full text |Cite
|
Sign up to set email alerts
|

Serial Thromboelastography and the Development of Venous Thromboembolism in Critically Ill Patients With COVID-19

Abstract: To test the hypothesis that relatively lower clot strength on thromboelastography maximum amplitude (MA) is associated with development of venous thromboembolism (VTE) in critically ill patients with COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…COVID-19 is also associated with thromboembolic disease, and increases the risk of venous and arterial thromboembolism events (Tomasoni et al 2020 ; Zhou et al 2020a ; Tang et al 2020 ; Ali and Spinler 2021 ; Danzi et al 2020 ; Wichmann et al 2020 ; Wichmann 2020 ; Gąsecka et al 2021 ; Kyriakoulis et al 2021 ; Heinrich et al 2022 ; Marvi et al 2022 ; Tsaplin et al 2021 ; Farkouh et al 2022 ; Epelbaum 2020 ; Takasu et al 2022 ; Hendren et al 2020 ). Both DIC and pulmonary embolism were very common in COVID-19 patients.…”
Section: Pathogenic Mechanisms Of Cardiovascular Damage In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 is also associated with thromboembolic disease, and increases the risk of venous and arterial thromboembolism events (Tomasoni et al 2020 ; Zhou et al 2020a ; Tang et al 2020 ; Ali and Spinler 2021 ; Danzi et al 2020 ; Wichmann et al 2020 ; Wichmann 2020 ; Gąsecka et al 2021 ; Kyriakoulis et al 2021 ; Heinrich et al 2022 ; Marvi et al 2022 ; Tsaplin et al 2021 ; Farkouh et al 2022 ; Epelbaum 2020 ; Takasu et al 2022 ; Hendren et al 2020 ). Both DIC and pulmonary embolism were very common in COVID-19 patients.…”
Section: Pathogenic Mechanisms Of Cardiovascular Damage In Covid-19mentioning
confidence: 99%
“…Platelet counts and fibrinogen levels were positively associated with maximum amplitude. The association between diminished maximum amplitude, platelet counts, fibrinogen and venous thromboembolism may suggest a relative consumptive coagulopathy in critical COVID-19 patients (Marvi et al 2022 ). Recently, the study by Tsaplin et al found that there was a significant correlation between the Caprini score and the risk of venous thromboembolism in COVID-19 patients.…”
Section: Pathogenic Mechanisms Of Cardiovascular Damage In Covid-19mentioning
confidence: 99%
“…Each 1 mm increase in baseline and peak MA was associated with a reduced risk of venous thromboembolism (reduced by 8% and 14%, respectively). Lower initial platelet counts and fibrinogen levels are also associated with an increased risk of venous thromboembolism, while platelet counts and fibrinogen levels are positively related to MA [ 75 ]. A consensus of the International COVID-19 Thrombosis Biomarkers Colloquium concluded that the viscoelastic test as a marker of coagulation and fibrinolysis may be useful in determining the prognosis of COVID-19-associated thrombosis.…”
Section: Diagnostic Markers Of Thrombosis In Covid-19 Patientsmentioning
confidence: 99%
“…The role played by serical and mucosal IgA responses, the total IgA generation rate from this response, and the involvement of its epitopes in COVID-19 severity and/or vaccination are largely poor explored areas [ 3 , 4 , 23 ] aside from notable instances such as frequent thromboembolisms in severe COVID-19 cases [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%